Pengaruh Program Kewirausahaan Terhadap Perekonomian Masyarakat Kabupaten Boalemo Provinsi Gorontalo - noerain wolango; irina popoi; agil bahsoan (Universitas Negeri Gorontalo, 2022)
His quantitative study aimed to identify the effect of the entrepreneurship program on the economy of the social village community in Paguyaman disttict, Boalemo Regency, Gorontalo Province.Employing a quantitative descriptive approach, this quantitative correlational study obtained primary data from questionnaires distributed to the villagers in the research site. The samples were retrieved using the Sugiono formula, which obtained 45 respondents, while the data analysis applied simple linear regression by using SPSS 21 program.The finding revealed that the variable X and Y’s t-tes results had a positive and significant effect on the economic improvement, which obtained 36%, meaning a better entrepreneurship program will improve the economy at the research site.